Power and positionality in the practice of health system responsiveness at sub-national level: insights from the Kenyan coast - Nancy Kagwanja; Sassy Molyneux; Eleanor Whyle; Benjamin Tsofa; Hassan Leli; Lucy Gilson (BMC, 2024)
Abstract Background Health system responsiveness to public priorities and needs is a broad, multi-faceted and complex health system goal thought to be important in promoting inclusivity and reducing system inequity in participation. Power dynamics underlie the complexity of responsiveness but are rarely considered. This paper presents an analysis of various manifestations of power within the responsiveness practices of Health Facility Committees (HFCs) and Sub-county Health Management Teams (SCHMTs) operating at the subnational level in Kenya. Kenyan policy documents identify responsiveness as an important policy goal. Methods Our analysis draws on qualitative data (35 interviews with health managers and local politicians, four focus group discussions with HFC members, observations of SCHMT meetings, and document review) from a study conducted at the Kenyan Coast. We applied a combination of two power frameworks to interpret our findings: Gaventa's power cube and Long's actor interface analysis. Results We observed a weakly responsive health system in which system-wide and equity in responsiveness were frequently undermined by varied forms and practices of power. The public were commonly dominated in their interactions with other health system actors: invisible and hidden power interacted to limit their sharing of feedback; while the visible power of organisational hierarchy constrained HFCs' and SCHMTs' capacity both to support public feedback mechanisms and to respond to concerns raised. These power practices were underpinned by positional power relationships, personal characteristics, and world views. Nonetheless, HFCs, SCHMTs and the public creatively exercised some power to influence responsiveness, for example through collaborations with political actors. However, most resulting responses were unsustainable, and sometimes undermined equity as politicians sought unfair advantage for their constituents. Conclusion Our findings illuminate the structures and mechanisms that contribute to weak health system responsiveness even in contexts where it is prioritised in policy documents. Supporting inclusion and participation of the public in feedback mechanisms can strengthen receipt of public feedback; however, measures to enhance public agency to participate are also needed. In addition, an organisational environment and culture that empowers health managers to respond to public inputs is required.